The labor market effects of outsourcing parts and components: adverse Cournot competition - Michael Hübler (Kiel Institute for the World Economy (IfW), 2009)
This paper contributes to Hübler (2008) who analyses a partial equilibrium model of outsourcing with Cournot competition in intermediate good production. Final production is located in Western Europe, whereas the intermediate good can be manufactured by a Western (outsourcing) or Eastern European supplier (offshore outsourcing). The paper asks the question how changes in production costs, in particular wages, affect output and thus labor input in the two regions. The paper proves analytically that under certain conditions higher production costs in one region reduce intermediate good production in both regions.
Keywords: D24; D43; F20; J31; 330; Offshoring; outsourcing; Cournot competition; intermediate goods; high-skilled; low-skilled; Offshoring; Outsourcing; Vorprodukt; Beschäftigungseffekt; Duopol; Theorie